Looking Inside the Dream Team: Probing Into the Contributions of Tacit Knowledge as an Organizational Resource - Shamsie, Jamal; Mannor, Michael J. (Organization Science, 2013)
Despite growing evidence that suggests that tacit knowledge can serve as a critical resource, there has been little effort to understand how such a form of personalized knowledge can provide strong advantages to an entire group or organization. In this paper, we develop four different categories of tacit knowledge that are derived from the basic tenants of the resource-based framework. More specifically, we distinguish between the discrete and linked forms of productive tacit knowledge that is possessed by individuals and administrative tacit knowledge that is held by managers within an organization. Next, we evaluate the role of each of these four different forms of tacit knowledge by focusing on the contribution of players and managers of professional sports teams. Our analysis of a large sample of Major League Baseball teams from 1985 to 2001 provides significant support for the importance of each of these categories of tacit knowledge for the performance of an organization.